The Effect of Internal Factor Toward Banking Credit Distribution - Pratiwi, Pratiwi; Muktiyanto, Ali; Yayuk Priyati, Rini (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2021)
The country's economy is supported by banking institutions. This is because the benefits of credit are greater compared to other bank businesses such as savings fund deposit services fees, interbank delivery service fees and so on. Internal factors that affect lending include CAR, ROA, NPL, LDR and BOPO. This research was conducted with the aim of simultaneously testing CAR, ROA, NPL, LDR and BOPO on bank credit distribution. The research sample is the bank with the largest number of assets in Indonesia. Data were obtained from the financial statements of the Persero's commercial banks from 2013 to 2017, using the panel data regression data analysis method. The results of hypothesis testing on CAR have a positive influence on lending, ROA also has a positive effect on lending, NPL has a negative effect, LDR has a positive effect, BOPO has a negative effect, whereas if tested simultaneously, CAR, LDR, NPL, LDR and BOPO has a positive effect on lending. With regard to the above conclusions, bank management should be able to take into account the trend of financial ratios for several years, before determining the lending policy